PENERAPAN FLIPBOOK UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI DI SMA NEGERI 3 MEULABOH - Fetro dola syamsu dola syamsu; Febry Fahreza; Iis Maningsih (LPPM Universitas Cipta Mandiri, 2026)
This study aimed to enhance the learning motivation of eleventh-grade students at SMA Negeri 3 Meulaboh through the implementation of flipbook-based learning media on the human movement system topic. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of two meetings. The research subjects were 23 eleventh-grade students, comprising 12 female and 11 male students. Data were collected through observations of students’ learning motivation and learning outcome evaluations. The results indicated that in Cycle I, students’ learning motivation was relatively low, with a mastery level of 40%. After instructional improvements were implemented in Cycle II through the optimized use of flipbook media, students’ learning motivation significantly increased, with 78% of students demonstrating good learning motivation. These findings indicate that flipbook-based learning media are effective in enhancing students’ learning motivation and can be utilized as an interactive instructional alternative in senior high school biology learning.